A morphometric and histological study of placental malaria shows significant changes to villous architecture in both Plasmodium falciparum and Plasmodium vivax infection - Chaikitgosiyakul, S; Rijken, M; Muehlenbachs, A; Lee, S; Chaisri, U; Viriyavejakul, P; Turner, G; Pongponratn, E; Nosten, F; McGready, R (BioMed Central, 2014)
BACKGROUND: Malaria in pregnancy remains a major health problem. Placental malaria infection may cause pathophysiological changes in pregnancy and result in morphological changes to placental villi. Quantitative histomorphological image analysis of placental biopsies was performed to compare placental villous architecture between active or treated placental malaria cases and controls. METHODS: A total of 67 placentas were studied from three clinical groups: control patients who did not have malaria (n = 27), active (n = 14) and treated (n=26) malaria cases, including both Plasmodium falciparum and Plasmodium vivax infections. Image analysis of histological placental sections was performed using ImageJ software to measure the number and size (area) of terminal villi, perimeter measurement per villus and total perimeter per unit area, and number of capillaries per villus (vascularity). Histological features of placental malaria were scored and these results were correlated with malaria status and clinical outcomes. RESULTS: Villous size correlated with vascularity (p <0.0001) but was inversely correlated with observed villi per unit area, (p = 0.0001). Significantly greater villous area and vascularity was observed in UK controls. Indices of histological malaria infection were significantly greater in active versus treated malaria cases. Active placental malaria cases showed significantly smaller villous area (p <0.0084), vascularity (p <0.0139) and perimeter (p <0.0006) than treated malaria cases or controls, but significantly more villi per unit area (p <0.0001). Villous size in treated malaria cases was significantly larger than active placental malaria cases (p <0.001) and similar to controls. There was a significant relationship between villous number and anaemia at the time of infection (p <0.0034), but not placental weight, birth weight or gestational age at delivery. No differences were found between histology or villous morphology comparing infections with P. falciparum or P. vivax. CONCLUSIONS: These results imply that villous size, perimeter and vascularity are acutely decreased during active placental malaria, decreasing the surface area available for gas exchange per villus. However the increased number of villi per unit area offsets this change and persists after treatment. Histopathological and villous architectural changes may be reversed by early detection and appropriate anti-malarial treatment.